Import activities at Dhaka Bank Ltd : Dhaka bank CPC-trade operation - Haque, Shad Md. Naturul (BRAC Univeristy, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2016.